2020
DOI: 10.3390/ani11010038
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Energy Partitioning and Methane Emissions in Murciano-Granadina Goats Fed Orange Leaves and Rice Straw as a Replacement for Beet Pulp and Barley Straw

Abstract: Considering the huge quantities of crops by-products and pruning waste such as rice straw and citrus leaves produced annually worldwide, and their potential pollution capacity, recycling as feed for livestock is an alternative. The objective was to study these by-products effect on energy balance and methane emissions in 10 Murciano-Granadina goats at maintenance. The control diet (CTR) included barley straw and beet pulp while the experimental diet (ORG) consisted of rice straw and orange leaves. Differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Lima et al [ 57 ] reported that when the level of concentrate inclusion in the diet exceeded approximately 50%, goats’ absolute CH 4 emission decreased. Feeding orange leaves and rice straw to Murciano–Granadina goats reduced CH 4 emissions without affecting energy balance [ 58 ].…”
Section: Alternative Feed Resources In Small Ruminant’s Nutritionmentioning
confidence: 99%
“…Lima et al [ 57 ] reported that when the level of concentrate inclusion in the diet exceeded approximately 50%, goats’ absolute CH 4 emission decreased. Feeding orange leaves and rice straw to Murciano–Granadina goats reduced CH 4 emissions without affecting energy balance [ 58 ].…”
Section: Alternative Feed Resources In Small Ruminant’s Nutritionmentioning
confidence: 99%